Evaluation foundations revisited : cultivating a life of the mind for practice - Schwandt, Thomas A. (Stanford Business Books, an imprint of Stanford University Press, 2015)
Evaluation examines policies and programs across every arena of human endeavor, from efforts to stop the spread of HIV/AIDS to programs that drive national science policy. Relying on a vast array of methods, from qualitative interviewing to econometrics, it is a ""transdiscipline, "" as opposed to a formal area of academic study. Accounting for these challenges, Evaluation Foundations Revisited offers an introduction for those seeking to better understand Evaluation as a professional field. While the acquisition of methods and methodologies to meet the needs of certain projects is important, th.